PENINGKATAN KINERJA PEGAWAI MELALUI PEMANTAPAN KOMPETENSI DI BADAN PUSAT STATISTIK KABUPATEN DELI SERDANG - Hidayati, Dika; Wulandari, Sari (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Employees are the most important aspect in the organization and HR is one of the drivers so that the organization can run well. Performance is an important element in determining the progress of an organization. The purpose of this study is to determine the role in improving employee performance through strengthening competence at the Central Bureau of Statistics of Deli Serdang Regency. This type of research uses descriptive research with a qualitative approach. The population and sample are employees of the Central Statistics Agency, Deli Serdang district. By using descriptive qualitative method. Data obtained through interviews with employees of the Central Statistics Agency of Deli Serdang Regency. The results obtained are that HR greatly determines employee performance and to produce competent employees, training, development from the organization and guidance from superiors will be needed so that the organization will advance for the better.